2022
DOI: 10.1155/2022/1187742
|View full text |Cite
|
Sign up to set email alerts
|

Low Prognostic Nutritional Index Contributes to High Adverse Events in Preeclampsia

Abstract: Background. Preeclampsia (PE) is a common obstetric complication that has caused significant harm to pregnant mothers. The clinical significance of poor nutritional status in PE patients is unclear. The aim of our study was to evaluate the nutritional status as measured by the prognostic nutritional index (PNI) score at admission, and its ability to predict in-hospitalization adverse events in patients with PE. Methods. We enrolled patients diagnosed with PE in the Third Affiliated Hospital of Guangzhou Medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Afterward, PNI gradually became a new predictor of the prognosis of many diseases. For example, low PNI contributes to high adverse events in preeclampsia [ 20 ]; it also can predict early mortality in diffuse large B-cell lymphoma [ 21 ]. Recent research even documented that PNI can be used to guide the clinician in predicting the 30-day mortality of patients diagnosed with delirium [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Afterward, PNI gradually became a new predictor of the prognosis of many diseases. For example, low PNI contributes to high adverse events in preeclampsia [ 20 ]; it also can predict early mortality in diffuse large B-cell lymphoma [ 21 ]. Recent research even documented that PNI can be used to guide the clinician in predicting the 30-day mortality of patients diagnosed with delirium [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prognostic nutritional index (PNI) is a simple index reflecting human nutritional and immunity levels [4]. Many studies have shown that the PNI can predict the prognosis of tumors [5,6], autoimmune diseases [7], chronic obstructive pulmonary disease (COPD) [8], acute heart failure [9], cardiomyopathy [10], and other diseases [11][12][13]. Nevertheless, there have been few and contentious studies on the relationship between PNI and AMI prognosis.…”
Section: Introductionmentioning
confidence: 99%